Improvement of Mesenchymal Stem Cell Immunomodulatory Properties by Heat-Killed Propionibacterium acnes via TLR2 - Silveira, Gabriela da Paz; Ishimura, Mayari Eika; Teixeira, Daniela; Galindo, Layla Tesla; Sardinha, Agnes Araujo; Porcionatto, Marimelia; Longo-Maugéri, Ieda Maria (Frontiers in Molecular Neuroscience, 2019)
Mesenchymal stem cells (MSCs) are an important tool for regenerative medicine, which aims to develop new technologies to improve their effects to obtain effective transplantation results. MSC immunomodulatory role has been demonstrated; however, how they react when they are stimulated by an adjuvant is poorly understood. Our group demonstrated the adjuvant effect of killed-Propionibacterium acnes (P. acnes) on hematopoietic stem cells. As these cells share the same MSCs bone marrow site and interact with them, here we evaluated the P. acnes and its soluble polysaccharide (PS) effect on murine MSCs and their immunomodulatory role in a murine model of traumatic brain injury. The bacteria increased the absolute number of MSCs, including MSC subpopulations, and maintained MSC plasticity. P. acnes and PS enhanced MSC proliferation and improved their immunomodulatory effect. P. acnes-MSC and PS-MSC transplantation increased anti-inflammatory cytokine expression and diminished pro-inflammatory cytokine expression after injury. This effect seemed to be mediated via TLR2 since P. acnes-KOTLR2-MSC transplantation decreased TGF-β and IL-10 expression. Increasing in neural stem cells and neuroblasts after PS-MSC transplantation was also observed. The adjuvant effect of P. acnes is an alternative means of increasing MSCs and important to identify their subpopulations to know better their role under exogenous stimuli including inflammation resolution in experimental model.